2015
DOI: 10.1128/jcm.00065-15
|View full text |Cite
|
Sign up to set email alerts
|

Human Diphyllobothrium nihonkaiense Infection in Washington State

Abstract: A patient in Washington State harbored a fish tapeworm most likely acquired from eating raw salmon. Diphyllobothrium nihonkaiense was identified by cox1 sequence analysis. Although this is the first documented human D. nihonkaiense infection in the United States, the parasite may have been present earlier but misidentified as Diphyllobothrium latum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Others species D. dalliae, D. lanceolatum, D. ursi, D. alascensis (syn. Diphyllobothrium alascense) (Rausch and Adams, 2000), and more recently D. nihonkaiensis have been responsible for human infections in the Pacific coast of North America (British Columbia, Canada and North-West, USA) (Wicht et al, 2008b;Fang et al, 2015). Recently, Kuchta et al (2017) reported plerocercoids of D. nihonkaiensis in the pink salmon, Oncorhynchus gorbuscha, from Resurrection Creek, Alaska.…”
Section: North Americamentioning
confidence: 99%
See 2 more Smart Citations
“…Others species D. dalliae, D. lanceolatum, D. ursi, D. alascensis (syn. Diphyllobothrium alascense) (Rausch and Adams, 2000), and more recently D. nihonkaiensis have been responsible for human infections in the Pacific coast of North America (British Columbia, Canada and North-West, USA) (Wicht et al, 2008b;Fang et al, 2015). Recently, Kuchta et al (2017) reported plerocercoids of D. nihonkaiensis in the pink salmon, Oncorhynchus gorbuscha, from Resurrection Creek, Alaska.…”
Section: North Americamentioning
confidence: 99%
“…It measures from 1 m to 12 m, but could be up to 25 m in D. latus species (Table 1). It could live 10 to 15 years, but an infection lasting about 30 years has been reported (von Bonsdorff, 1977 Andersen, 1971Andersen, , 1975Andersen et al, 1987;von Bonsdorff, 1977;Dick and Poole, 1985;Kamo, 1999;Kuchta et al, 2015b;Rausch and Hilliard, 1970;Scholz et al, 2009;Torres, 2013;Torres et al, 1989aTorres et al, , 1993Yamane et al, 1989a;Yazaki et al, 1984; b Ando et al, 2001;Arizono et al, 2009b;Choi et al, 2015;Fang et al, 2015;Jeon et al, 2009;Kamo, 1999;Wicht et al, 2008b;Yamane et al, 1986;Yamasaki and Kuramochi, 2009;Yera et al, 2006;c Andersen, 1975;Andersen et al, 1987;Dick and Poole, 1985;Figueroa et al, 1979Figueroa et al, , 1980Kuchta et al, 2013;Rausch and Hilliard, 1970;Torres et al, 1981b; d Baer et al, 1967;Cattan et al, 1977;Escalante and Miranda, 1986;Hernández-Ortz et al, 2015;Jacobus et al, 2016;Jimenez et al, 2012;Kuchta et al, 2015b;…”
Section: Symptomatology Morbidity and Mortalitymentioning
confidence: 99%
See 1 more Smart Citation
“…The sources of infection for these cases are suspected to be the salmon imported from North America ( 27 ). Furthermore, regardless of immunity, anyone can get infected with D. nihonkaiense tapeworm in the countries where the pathogen exists, such as Korea ( 29 , 30 ), China ( 26 , 31 ), the United States ( 32 ), Canada ( 33 , 34 ), and eastern Russia ( 35 ). …”
Section: Perspectives Of Diphyllobothriasismentioning
confidence: 99%
“…For decades, the possible occurrence of the Japanese broad tapeworm on the Pacific coast of North America was ignored, but since 2008, human infection with adult tapeworms and natural infection of carnivores (wolves and bears) with adult tapeworms have been confirmed by use of molecular markers ( 1 , 8 10 ). We report finding Japanese broad tapeworm plerocercoids in North America.…”
mentioning
confidence: 99%